Following the application of podocarp training in the biomechanical indicators of triple jump athletes - Hussein, Prof. Dr. Ahlam Sadiq (Sulaimani Journal for Humanities, 2026)
The importance of this research lies in the researcher's finding of a real problem in the biomechanical indicators of triple jumpers, which consequently affects their performance. Through her observations of triple jumpers, the researcher, specializing in track and field events, found a need for modern training methods to improve their biomechanical indicators. She discovered the effectiveness of using boot camp exercises in this regard, prompting her to investigate modern methods and discover boot camp exercises.
Keywords: Boot camp (podocarp) training